Spectrophotometric Determination of Metformin in Different Pharmaceutical Combinations With Glipizide or Sitagliptin in Presence of Toxic Impurities of Metformin - Abdallah, Fatma F; Magdy, Fatma; Abdelaleem, Eglal A; Emam, Aml A (Journal of AOAC International, 2022)
The presented quadruple divisor spectrophotometric method was able to resolve and analyze a complex quintuple drug matrix with severe overlapped spectra without previous separation or extraction steps or need of complicated apparatus like chromatographic methods and had the advantage of being green as the solvent used was water. A simple, sensitive, and precise quadruple devisor spectrophotometric method was developed for simultaneous determination of metformin, glipizide, and sitagliptin in the presence of metformin potential impurities melamine and cyanoguanidine. The proposed method was applied for analysis of metformin, glipizide, and sitagliptin in pure form and pharmaceutical formulation (tablets). The developed method was validated and met the requirements for ICH guidelines with respect to linearity, accuracy, precision, specificity, and robustness. A linear response was observed in the range of 2-27, 2-20, 1-20, 0.5-10, and 1-10 μg/mL for metformin, glipizide, sitagliptin, melamine, and cyanoguanidine, respectively, with a correlation coefficient of 0.9996, 0.9998, 0.9997, 0.9997, and 0.9996 for metformin, glipizide, sitagliptin, melamine, and cyanoguanidine, respectively. The validated method was successfully applied for determination of the studied drugs in Janumet® and Engilor® tablets; moreover, the results were statistically compared to those obtained by the reported RP-HPLC method and no significant difference was found between them, indicating the ability of the proposed method to be used for routine quality-control analysis of these drugs. Novel application of quadruple divisor spectrophotometric technique is introduced for resolving mixtures containing five components with severely overlapping spectra. A simple and sensitive spectrophotometric method was developed for simultaneous determination of metformin, glipizide, and sitagliptin in the presence of metformin potential impurities melamine and cyanoguanidine. The validity of the proposed method was revealed as per ICH guidelines.